The influence of nutrition on the percentage of fat tissue among students of University of Physical Education in Krakow - Madejski, Przemysław; Bac, Aneta; Madejski, Roger (Health Promotion & Physical Activity, 2019)
Introduction: Adequate nutrition is one of the most important environmental factors that have an influence on human development and maintaining good health condition. It consists in meeting the demand of an organism for energy and all the necessary nutrients completely. Material and methods: The survey was conducted in 2014. It covered 93 second year Physiotherapy and Physical Education students (48 females and 45 males) in Bronisław Czech University of Physical Education in Kraków. The average age of the surveyed students was 21. The Tanita scales were applied to define the value of BMI and to calculate the percentage of fat tissue in the organism. Results: The research results have revealed that the respondents represent an average and good manner of nutrition. The majority of the subjects (73.1%) had a normal percentage of fat tissue. While examining the relations between the way of nutrition and fat percentage, it was found that 50% of females who fed themselves well had a low FAT%. Only 13.7% of males representing an average interval of nutrition manner were found to have a high percentage of fat tissue. Among the majority of the respondents (79.6%) the BMI level was within the norm. Overweight was more frequent among males than females, whereas underweight vice versa. Conclusions: The majority of the surveyed students feed themselves in an average manner. The manner of nutrition had a significant influence on body fat only among females. The majority of respondents’ BMI level was within the norm.